An Analysis of Slang Words in Ant Man Movie - Yenni Rosana; Merry Rullyanti; Iduwan Iduwan; Anisa Ernatri Hamnasthia (UNIVED Press, 2019)
The title of this study is Slang Word Used in Movie “Ant-Man”. The aims of the study are to identify the types of slang and meaning conveyed in movie Ant-Man. The data of this study were collected from” Ant-Man” movie as the data source. The theories used in the study are theory proposed by Allan and Burridge (2006) entitled Forbidden words: Taboo and The Censoring of Language used to identify the types of slang word, and theory proposed by by Leech (1974) entitled Study of Meaning used to analyze the meanings conveyed in the movie. The documentation method is used to collect the data, and derive qualitative method is used to analyze the data. There were forty slangs either in the form of words or phrases that are analyzed based on theory mentioned above. There are five types of slang in theory of Allan and Burridge (2006) but only four types were found in the movie. Those are fresh and creative, imitative, flippant, acronym, and clipping. Flippant type was the most found in the data source. For the meaning, there were seven types of meaning based on the theory proposed by Leech (1974) but only six types were found in the movie. Those are conceptual meaning, connotative meaning, social meaning, collocative meaning, reflected meaning, and affective meaning. Affective meaning type is the most found in the data source. Keywords: slang words, type of slang, meaning, Ant-Man